The Degree of Compatibility between Higher Education Policies and the Needs of Labor Market in Saudi Arabia - Norah Al-Azzam (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the degree of compatibility between education policies in higher education institutions in the Kingdom of Saudi Arabia and the needs of the labor market. The study population consist of all university administrators and their assistants, and heads of councils of chambers of commerce and industry in the Kingdom. A descriptive and analytical approach was used. A tool (a questionnaire) was developed, which consisted of (25) items, and was then distributed to a sample of (250) university administrators and their assistants, and heads of the councils of chambers of commerce and industry in the Kingdom, after its validity and reliability were confirmed. The results of the study showed that the assessment of the degree of education policies in higher education institutions in the Kingdom of Saudi Arabia and the needs of the labor market was of a moderate degree. There were no statistically significant differences in the degree of compatibility between education policies in higher education institutions in the Kingdom of Saudi Arabia and the needs of the labor market attributed to gender, educational level or job. The study recommends the necessity of taking into account the reasons that lead to the lack of harmonization netween education policies in higher education institutions in the Kingdom of Saudi Arabia and the needs of labor market.